Cooperative Model Approach to Students` Achievement in Malay Essay Writing - Sulaiman, Muhamad Fitri; Banseng, Saripah (International Journal of Pedagogy and Learning Community (IJPLC), 2024)
This study was carried out to see the effectiveness before and after the use of the cooperative model approach on the achievement of students in writing summary essays in Malay. In addition, this study was also carried out to analyse the differences that existed before and after the use of the cooperative model on the achievement of students in the writing of summary essays in Malay. A total of 30 respondents consisting of students from a 4th-grade class were involved in implementing this study as a sampling purpose. This study uses cognitive development theory as a guide in cultivating 21st-century learning practices (PAK-21) in the classroom. This study uses a descriptive quantitative method in the form of a test. 30 sets of pre and post-test questions were given to all respondents involved as an instrument in this study. The data for the pre-and post-test instruments were analysed using the Statistical Package for Social Science (SPSS) software. The results of the study found that there is a significant relationship between students' achievement in the writing of summary essays in Malay before and after the use of the cooperative model approach. The results of the study also show that there is a positive development in the performance of students in writing summary essays in Malay after the cooperative model approach is applied (mean=88.40). This indirectly proves that the use of the collaborative model approach is relevant and able to improve the performance of students in the teaching of Malay summary essays. This study is expected to be a reference source for other researchers and Malay language teachers to make teaching activities more creative and effective.